1985
DOI: 10.1111/j.1600-0897.1985.tb00334.x
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of the Inhibitory Effect of Progesterone on Lymphocyte Cytotoxicity: I. Progesterone‐Treated Lymphocytes Release a Substance Inhibiting Cytotoxicity and Prostaglandin Synthesis

Abstract: Progesterone-treated lymphocytes (generator lymphocytes) of healthy pregnant women release a nondialyzable factor that inhibits both cytotoxic activity and prostaglandin F2 alpha synthesis of test lymphocytes. Production of this factor is blocked by protein synthesis inhibitors (cycloheximide and actinomycin D). Sodium dodecylsulfate polyacrylamide electrophoresis of the partially purified material revealed a main 34,000 MW protein band. Progesterone-treated lymphocytes of pregnant women showing clinical sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(53 citation statements)
references
References 16 publications
5
46
0
2
Order By: Relevance
“…However, no conserved splice site or coding mutations were identified in this gene. PIBF1 is a lymphocyte-secreted immunomodulatory molecule 41 that is expressed in spleen 35 and overexpressed in breast tumor cell lines. 42 PIBF1 is a microtubuleassociated protein that localizes to centrosomes, 42 where abnormalities are frequently observed in cancer cells, although their role in tumorigenesis is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, no conserved splice site or coding mutations were identified in this gene. PIBF1 is a lymphocyte-secreted immunomodulatory molecule 41 that is expressed in spleen 35 and overexpressed in breast tumor cell lines. 42 PIBF1 is a microtubuleassociated protein that localizes to centrosomes, 42 where abnormalities are frequently observed in cancer cells, although their role in tumorigenesis is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…13 PIBF was originally described as a 34 kDa protein. 1 Expression cloning with antibodies generated against this secreted form identified a transcript corresponding to a 90 kDa protein encoded by 18 exons 5 that seems to be the predominant PIBF mRNA form. In Western blot analyses using PIBF-specific antibodies, we consistently detected an approximately 90 kDa protein, which represented the dominant PIBF protein form in all tissues and cell lines tested.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, previous protein expression studies revealed that PIBF was also expressed by the progesterone receptor positive human mammary carcinoma cell line, MCF-7. 5 An extensive BLAST search analysis of the cloned PIBF mRNA sequence using the human dEST library database (http://www.ncbi.nlm.nih.gov/ BLAST, est_human database) suggested a more universal expression and revealed that PIBF mRNA is expressed not only in lymphocytes but also in many other cell types, mainly in embryonic tissues, pregnant uterus, placenta and testis (ϳ 30% of all entries).…”
Section: Overexpression Of Pibf Mrna In Malignant Tumorsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previously we reported that Progesterone-Induced Blocking Factor (PIBF) is secreted by maternal lymphocytes and mediates the immunological effects of progesterone during pregnancy [4,5]. PIBF inhibits Natural Killer (NK) cell activity and enhances Th2-type cytokine production via the JAK1/STAT6 and PKC/Ca++ pathways [6,7], thus supports the maintenance of pregnancy.…”
Section: Introductionmentioning
confidence: 99%